2014
DOI: 10.1159/000367891
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Sex Manifestations in Hysteria Across Medicine and the Arts

Abstract: The diagnosis of hysteria has existed for at least four-thousand years, with roots in the ancient Greek word hysterikos, referring to diseases of the womb. In the sixteenth-century medical discourses, female hysteria was caused by excess pollution of the womb, with fluids that were labelled ‘female sperm' as the probable cause. In the work of Shakespeare, there is a reference to hysterica passio, a term used by King Lear to self-diagnose his affliction. Shakespeare shows how a disease associated with women, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…(1) Boys seemed to have a lower AR than girls, suggesting that gender may affect the risk of MH in children and adolescents. 40 The ARs for MH in boys and girls in the present study were very similar to those reported in previous studies. 40 , 41 Many studies 40 42 have shown that women/girls are more likely than men/boys to experience hysteria.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…(1) Boys seemed to have a lower AR than girls, suggesting that gender may affect the risk of MH in children and adolescents. 40 The ARs for MH in boys and girls in the present study were very similar to those reported in previous studies. 40 , 41 Many studies 40 42 have shown that women/girls are more likely than men/boys to experience hysteria.…”
Section: Discussionsupporting
confidence: 91%
“… 40 The ARs for MH in boys and girls in the present study were very similar to those reported in previous studies. 40 , 41 Many studies 40 42 have shown that women/girls are more likely than men/boys to experience hysteria. (2) The meta-analysis identified three main trigger factors for MH in children and adolescents: water pollution, suspected food poisoning and supernaturalism.…”
Section: Discussionsupporting
confidence: 91%
“…This correlation was established in ancient Greece because most cases of hysteria occurred in women, but only in the 16 th century the term hysteria was regularly applied to designate such functional disorders. 1 2 3 4…”
Section: Introductionmentioning
confidence: 99%
“…A similar situation to the one experienced by patients with other neurological conditions, such as stroke and epilepsy. 1 2 3 4…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation